Clinical Cases in Integrative Dermatology - Norman, Robert A.; Rupani, Reena (Clinical Cases in Dermatology, 2015)
This book serves as a useful clinical guide on integrative dermatology for dermatologists, internists, family practitioners, pediatricians, and anyone else charged with the care of the skin. The case-based format distinguishes this work from a reference-style textbook, allowing readers to relate the presented cases to their own patients. Integrative dermatology is a relatively newly-defined field but is steadily increasing in popularity. Clinical Cases in Integrative Dermatology provides insight for clinicians and patients in handling the skin, with each chapter serving as a springboard for further pursuit and more extensive training.  It will enable those new to the field to begin to develop a literacy and competence, while the more experienced learner will find new ways to sharpen their diagnostic and treatment skills.